MERCY KILLING IN CONTEMPORARY CRIMINAL LAW - Jovašević, Dragan M. (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Violent acts against the life and physical integrity of others are certainly among the most dangerous forms and manifestations of violent crime. These are blood crimes, among which, by their importance, nature, characteristics and consequences, are the crimes of murder, for which severe penalties have been imposed in all modern criminal legislation. There are three types of homicide. These are: a) ordinary murder, b) privileged homicide, and c) grave or qualified homicide for which the most severe punishment is prescribed. Numerous contemporary criminal legislation in Europe, as well as the legislation of the Republic of Serbia, know about specifically privileged murder. That is: murder out of compassion, mercy, noble motives, or murder at the request of the injured party, as this act is called in individual laws. It is precisely the concept, content and special characteristics of this privileged murder in Serbian law, but also in European criminal law, from a theoretical and practical point of view, that this paper discusses.
Keywords: life; deprivation; law; crime; murder; compassion; victim's claim; responsibility; punishment